Student Management in Improving Student Learning Ethos (Case Study at MTs NU Sumber Agung) - Hamzatul Munir; Rizki Novita; Nurrana Fitria Luthfi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
The learning ethos is a reflection of students' behavior during learning. In an effort to improve the learning ethos, it is necessary to implement programs, one of which is through student management activities. This research aims to analyze the role of student management in improving students' learning ethos in secondary schools. A descriptive qualitative approach, this research collects data through observation, interviews with teachers, student affairs staff and students. Management strategies which include enforcing discipline and giving awards play an important role in improving the learning ethos of MTs NU Sumber Agung students. It is known for its excellent religious education and its well-educated students who have good morals and are able to have a positive impact on their peers. The techniques chosen in data analysis are data reduction, data presentation and drawing conclusions. The results of this research are: (1) Student planning is carried out in the form of creating a New Student Admissions Committee (PPDB), preparing PPDB planning (planning numbers, classrooms, making brochures and registering new students), and preparing learning plans until student graduation. (2) Implementation of student affairs includes accepting new students, grouping students, recording student attendance, as well as coaching and developing students. (3) Evaluation of students at MTs NU Sumber Agung is carried out at every activity, such as after daily tests, when distributing semester exam study scores.